1999
DOI: 10.1097/00007632-199907010-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lumbar Fatigue on the Ability to Sense a Change in Lumbar Position

Abstract: Lumbar fatigue impairs the ability to sense a change in lumbar position. This feature was found in patients and control subjects, but patients with low back trouble had poorer ability to sense a change in lumbar position than control subjects even when they were not fatigued. There seems to be a period after a fatiguing task during which the available information on lumbar position and its changes is inaccurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
172
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(190 citation statements)
references
References 26 publications
12
172
1
3
Order By: Relevance
“…This can be explained by the negative influence of fatigue on the muscle receptors and thereby on proprioception [2,14]. Due to lumbar muscle fatigue, proprioceptive acuity can decrease, which leads to inaccurate signals about lumbar spine position and movement [19]. Under simple (nonfatigued) postural conditions, greater dependence upon proprioceptive input from the ankles is the norm, and increased input from back muscle spindles only becomes important when the stance is unstable, in which case healthy controls adapt their strategy accordingly but people with LBP do not.…”
Section: Back Muscle Fatigue Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by the negative influence of fatigue on the muscle receptors and thereby on proprioception [2,14]. Due to lumbar muscle fatigue, proprioceptive acuity can decrease, which leads to inaccurate signals about lumbar spine position and movement [19]. Under simple (nonfatigued) postural conditions, greater dependence upon proprioceptive input from the ankles is the norm, and increased input from back muscle spindles only becomes important when the stance is unstable, in which case healthy controls adapt their strategy accordingly but people with LBP do not.…”
Section: Back Muscle Fatigue Conditionmentioning
confidence: 99%
“…The fatigue-related changes in muscle stiffness may reduce the capacity of the paraspinal muscles to stabilize the spine [18]. Furthermore, Taimela et al concluded that lumbar muscle fatigue impaired lumbar position sense in patients with LBP and healthy subjects [19]. Some studies showed that lumbar extensors fatigue resulted in an increased postural sway in healthy individuals [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…But fatigue also poses other more subtle dilemmas for the spine system. Fatigue has been shown to impair spine proprioception (Taimela et al, 1999) and the ability to regulate force (Parnianpour et al, 1988;Sparto et al, 1997). Recently, we conducted an experiment that showed trunk muscle force variability increases after a fatiguing trial, and like others found that fatigue also produces more trunk muscle co-activation (O'Brien and Potvin, 1997;Potvin and O'Brien, 1998;Granata et al, 2004b).…”
Section: Controller Related Impairmentmentioning
confidence: 74%
“…As proprioception constitutes one of the sensory inputs for regulation of postural stability, defective input may affect the accuracy of postural control. Previous studies reported that LBP subjects are less sensitive to detect rotary motion in both detections 21 , make errors with reproduction of a previously presented lumbopelvic angle 22 , and consistently tend to undershoot target angles during active repositioning of sacral tilt 23 . If the quality of proprioceptive feedback from the lumbar spine is poor, control of the CoM position might become ineffective when the lumbopelvic movement is involved in postural control (i.e.…”
Section: Inferior Quality Of Postural Recovery In People With Lbpmentioning
confidence: 87%